The place of customs and traditions in women's issues in kazakh society in 20-30 years of ХХ century (Journal of history, 2023)
Abstract. The article is devoted to the situation and problems of Kazakh women in the transition to a new model of socio-political social construction in the early twentieth century. The authors in the article draw attention to the inequality in the social problems of Kazakh women in society before the October Revolution - on the one hand, in connection with Kazakh customs and traditions. The inequality of Kazakh women in selling for kalym, polygamy, the marriage of underage girls, for whom kalym was paid, with the elderly men and their status as second, third wives, becoming a victim of levirate customs, etc. everyday situations were covered on the pages of the archive, the press ("Ak Zhol", "Ayel tendigi", etc.). One of the first tasks of the Soviet government in the transition to a new model of social construction was the issue of "equality of women". In the course of establishing socio-political equality in achieving women's equality, several laws and regulations were adopted. In the article, the authors note that the patriarchal society did not immediately recognize the problem of equality of women of the Kazakh people, and also try to show by giving concrete examples that the problem of inequality of Kazakh women continued to exist in the 1930s, and even in the 1950s.Keywords: Kazakh society, women's issue, kalym, polygamy, levirate, customs, traditions.